The Significance of Intercurrent Remedy in Management of Allergic Rhinitis: A Case Report (Advancements in Homeopathic Research, 2022)
Allergic Rhinitis is a very common disorder that  affects people of all ages. It affects quality of life  and productivity at work or school. Medication for  Allergic Rhinitis are histamines and topical steroids,  which suppresses the body immune response to  allergens. Homoeopathy offers a mode of therapy that  is individualized to the patient without compromising  immunity of patient.
Keywords: Intercurrent Remedy; Allergic Rhinitis; Medication; Homoeopathy